2021
DOI: 10.1039/d0fd00086h
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the background and local contribution of the oxidants in London and Bangkok

Abstract: The contribution of NOx emissions and background O3 to the sources and partitioning of the oxidants [OX(=O3+NO2)] at the Marylebone Road site in London during the 2000s and 2010s has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…Previously, fleet technology improvement, such as the introduction of the 1992 catalytic convertors legislation, requiring all petrol vehicles to be fitted with catalytic convertors, which likely also led to 'cleaner' emissions [8]. Decreasing trends of other pollutants found in vehicle emissions, such as NO x , are consistent with this data, supporting the influence of advanced technology [46]. Furthermore, multiple emission control strategies were introduced in line with the London Mayor's Air Quality Strategy in 2010, including the implementation of the London Low Emission Zone (LEZ), congestion charging, and diesel-electric hybrid buses [47,48].…”
Section: Resultssupporting
confidence: 69%
“…Previously, fleet technology improvement, such as the introduction of the 1992 catalytic convertors legislation, requiring all petrol vehicles to be fitted with catalytic convertors, which likely also led to 'cleaner' emissions [8]. Decreasing trends of other pollutants found in vehicle emissions, such as NO x , are consistent with this data, supporting the influence of advanced technology [46]. Furthermore, multiple emission control strategies were introduced in line with the London Mayor's Air Quality Strategy in 2010, including the implementation of the London Low Emission Zone (LEZ), congestion charging, and diesel-electric hybrid buses [47,48].…”
Section: Resultssupporting
confidence: 69%
“…The strong reduction of anthropogenic emissions during the COVID19 lockdowns showed that only highly urbanized areas experienced an increase in O 3 concentration associated with a decrease in NOx concentration of up to 30%, while oxidant levels remained stable (e.g., Deroubaix et al, 2021;Gaubert et al, 2021). Misrepresentation of anthropogenic emissions in air quality models can lead to a bias in modeled oxidant level in megacities (e.g., Khan et al, 2021). However, the observed increases in O 3 concentrations during the COVID19 pandemic in São Paulo and even in Rio de Janeiro (e.g., Beringui et al, 2022;Nakada & Urban, 2020), are not reproduced by the global simulations performed by Gaubert et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…As such, VOCs are classified as air pollutants and some legislative interventions have been introduced in an attempt to limit their ambient concentrations 11 . However, the adverse effects extend beyond their direct effects 12 . The formation of secondary pollutants, such as ozone and particulate matters, have significant health, climate, and air quality impacts 13–19 .…”
Section: Introductionmentioning
confidence: 99%
“…11 However, the adverse effects extend beyond their direct effects. 12 The formation of secondary pollutants, such as ozone and particulate matters, have significant health, climate, and air quality impacts. [13][14][15][16][17][18][19] Whilst VOC air quality objectives (AQOs) are generally met across the UK (though explicit AQOs for VOCs are admittedly scarce 11 ), ambient ozone levels continue to exceed long-term AQOs.…”
Section: Introductionmentioning
confidence: 99%